Penerapan Konseling Berbasis Budaya Minangkabau - Betri yulita, Betri Yulita; Silvianetri, Silvianetri silvianetri; Elviana, Elviana elviana (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2021)
This study aims to describe culture-based counseling by integrating the cultural values of Minang Kabau with the counselee's problems. The method used is a systematic review through review articles using inclusion and exclusion criteria. Article searches are accessed from internet searches in the database, namely: Google engine, Google Scholar and Google Books with the keyword Minang Kabau culturebased counseling. Data analysis is by collecting articles that meet the inclusion criteria are collected and examined systematically. The search for literature published from 2015 to 2020. The results showed that Minangkabau culture-based counseling can and is effective to be applied in the counseling process.